The physiological demands of table tennis: A review - Kondrič, Miran (2013)
Although table tennis has a tradition lasting more than 100 years, relatively little is known about players' physiological requirements - especially during competition. In this review we discuss research studies that have led to our current understanding of how the body functions during table tennis training and competition and how this is altered by training. Match and practice analysis of the table tennis game indicates that during intense practice and competition it is predominantly the anaerobic alactic system that is called into play, while the endurance system is relied on to recovery the anaerobic stores used during such effort. It is thus important for coaches to keep in mind that, while the anaerobic alactic system is the most energetic system used during periods of exertion in a table tennis game, a strong capacity for endurance is what helps a player recover quicker for the following match and the next day of competition. This paper provides a review of specific studies that relate to competitive table tennis, and highlights the need for training and research programs tailored to table tennis. © Journal of Sports Science and Medicine.